AN EXAMINATION OF STUDENT TRAJECTORIES RELATED TO READING AND ATTENTION SKILLS ACROSS ELEMENTARY GRADES - Gonzales, Christine (East Carolina University, 2019)
Research on reading is widespread given its predictive nature for adult outcomes pertaining to success, such as high school graduation, college entrance, health literacy, employment status and wages earned. Research focusing on attention and attention-problems is also widespread, as attention has been found to be an integral part of the learning process. Previous research demonstrates that problems in reading and attention, individually, are associated with negative outcomes, and the prognosis for children who possess deficits in both areas is significantly worse. Furthermore, the relationship between reading and attention problems may be bi-directional in nature. However, there have been many limitations to previous studies and no study, as of yet, has examined the unique growth trajectories regarding both attention and reading performance of students throughout elementary school. Data for this study were drawn from the Early Childhood Longitudinal Study (ECLS-K) and focused on 16,970 students who had complete data for reading and attention variables at 1st, 3rd, and 5th grade. The findings indicate five growth trajectories with respect to reading and attention skills over the course of elementary school. These results remained consistent even after controlling for students' gender and SES quintile in 1st grade. Specifics regarding each of the five trajectories as well as implications for research and practice are discussed.
Keywords: Attention; Growth Mixture Modeling; Reading comprehension--Ability testing; School children; Reading (Elementary)